Odolnost FRP kompozitních materiálů vůči působení vybraných agresivních prostředí - Mičkal, Petr (Vysoké učení technické v Brně. Fakulta stavební, 2020)
Diplomová práce se zabývá sledováním trvanlivosti FRP výztuží v alkalickém prostředí při různých teplotách expozice. V teoretické části diplomové práce je obecný popis FRP kompozitů, výroba FRP výztuží technologii pultruze, odolnost těchto kompozitu v agresivní alkalickém prostředí a vliv teploty na rychlost a způsob degradace. V experimentální části této diplomové práce byly FRP výztuže uloženy v alkalickém prostředí a temperovány na různou teplotu (20 °C, 40 °C, 60 °C). Následně byly popsány a vyhodnoceny optické a fyzikální změny výztuží za použití optické mikroskopie a destruktivních zkoušek výztuží.

This thesis deals with monitoring of the durability of FRP reinforcements in alkaline environments with differing temperature exposures. The theoretical part of the thesis consists of a general description of the FRP composites, the manufacturing of these FRP reinforcements using pultrusion technology, the resistance of these composites in aggressive alkaline environments, and the influence of temperature on the speed and manner of degradation. In the experimental part of this thesis, the FRP reinforcements were placed in an alkaline environment tempered at different temperatures (20 °C, 40 °C, 60 °C). Subsequently, any optical physical changes of the reinforcements were described and evaluated by the use of optical microscopy and the destructive tests of these reinforcements.
FRP composite materials resistance to the effects of selected corrosive environments
Keywords: FRP; vlákny vyztužený polymer; trvanlivost; degradace; alkalické prostředí; vliv teploty; optická mikroskopie; krípová zkouška; FRP; fiber-reinforcement polymer; degradation; durability; alkaline environment; influence of temperature; optical microscopy; creep test